Sperm morphological abnormalities in autosomal dominant polycystic kidney disease are associated with the Hippo signaling pathway via PC1 - Shi, Wei-Hui; Zhou, Zhi-Yang; Ye, Mu-Jin; Qin, Ning-Xin; Jiang, Zi-Ru; Zhou, Xuan-You; Xu, Nai-Xin; Cao, Xian-Lin; Chen, Song-Chang; Huang, He-Feng; Xu, Chen-Ming (Frontiers in Endocrinology, 2023)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary kidney disorder resulting from mutations in PKD1 or PKD2 genes. Here, we reported thirteen ADPKD males suffering from infertility and investigated the microtubule abnormalities associated with disruptions of PC1 in vitro. Methods: The targeted next-generation sequencing was performed to detect PKD1 variants in patients. The sperm morphology was observed by immunostaining and transmission electron microscopy and the sperm motility was assessed by computer-assisted sperm analysis system. The Hippo pathway was analyzed with quantitative reverse transcription polymerase chain reaction (PCR) and western blotting in vitro. Results: The ADPKD patients were infertility and their sperm tails showed morphologic abnormalities, including coiled flagella, absent central microtubules, and irregular peripheral doublets. Moreover, the acetylation of α-tubulin in sperms was remarkably reduced in ADPKD. In vitro, decreased acetylated α-tubulin was also observed in Pkd1-depleted cells. Absence of PC1 resulted in reductions of MST1 and LATS1, which led to nuclear accumulation of YAP/TAZ and consequently increased transcription of AURKA. Ultimately, the reduced MST1 and increased AURKA would promote HDAC6-mediated tubulin deacetylation. Conclusions: Our results suggested that the dysregulated Hippo signaling prominently contributed to ciliary anomalies in ADPKD and was potentially associated with axonemal defects in sperm.